Evaluation of the Implementation of Biology Learning Assessment on the Concept of Environmental Pollution in the Merdeka Curriculum for Grade VIII Junior High School Students - Ari Susilowati; Hendro Prasetyono (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to evaluate the implementation of Biology learning assessment on the concept of environmental pollution in the Merdeka Curriculum for Grade VIII junior high school students. The evaluation was conducted on the implementation of diagnostic, formative, and summative assessments applied by the teacher during the learning process. This study employed an evaluative approach using Stake’s Countenance evaluation model, which includes the stages of antecedents, transactions, and outcomes. The research subjects consisted of one science teacher and 32 Grade VIII junior high school students. Data were collected through observation, document analysis, questionnaires, and interviews. The data were analyzed using descriptive quantitative and qualitative methods by comparing actual conditions with the assessment standards in the Merdeka Curriculum. The results showed that the implementation of Biology learning assessment on environmental pollution material was in the good category, with an average implementation rate of 83.2%. Diagnostic assessment obtained a score of 78.5%, formative assessment 85.6%, and summative assessment 85.4%. Nevertheless, challenges were still found in the implementation of non-cognitive diagnostic assessment and the provision of individual feedback to students. This study recommends the development of more authentic assessments that are oriented toward students’ learning needs in accordance with the principles of the Merdeka Curriculum.